Geopolitical positioning of twin cities - Okunev, igor Y. (Teorija in praksa, 2017)
This paper assesses the twin cities phenomenon in the categories of critical geopolitics based on cases such as Narva/Ivangorod, Valga/Valka and Blagoveshchensk/Heihe. The findings show that, despite the different locations, these city pairs demonstrate similar patterns in their spatial relations; in particular, the Russian twin in contrast to the non-Russian twin on the Estonian-Latvian border construct its border identity using ideas of "fortress"/"nation outpost", while its 'sibling' sees itself as a friendly, ready-to-cooperate neighbour. The findings apply to both the situation of the closed border between two towns where the ethnic Russian population dominates (Narva/Ivangorod on the Russian-Estonian border) and the contact border between ethnically non-mixed towns (Blagoveshchensk/Heihe on the Russian-Chinese border).
Keywords: Borderlands; Cities and towns; Geopolitics; Geopolitika; Mesta; Obmejna območja; Rusija; Russia